Novel Metal Electrodeposition and the Recent Application - Sone, Masato; Masu, Kazuya (IntechOpen, 2019)
Gold and noble metals have been attractive to humans from ancient times because of their beautiful features. In modern society, noble metals, especially gold, play important roles as components in electronic devices because of their high electrical conductivity, chemical stability, and density. In the field of MEMS devices, the demand for continuous miniaturization and sensitivity enhancement is always high. Especially for MEMS accelerometers, sensitivity is affected by Brownian noise, and components with sufficient mass are needed to suppress this noise. Therefore, it is difficult to reduce the dimensions of components to allow further miniaturization of the device. This book presents recent progress in noble metal electrodeposition and applications of gold-based materials in the realization of highly sensitive CMOS-MEMS accelerometers.